Environmental sustainability in transatlantic perspective : a multidisciplinary approach - Achilles, Manuela, 1968-; Elzey, Dana M. (New York, NY : Palgrave Macmillan, 2013)
'The task of building more energy-efficient, climate-friendly and sustainable societies is the defining challenge of the 21st century. Striving to become the world's first major renewable energy economy by 2050, Germany is a global front runner in environmental policy and practice. Requiring massive investments in green technologies and infrastructure, Germany's ambitious shift from fossil fuels and nuclear power to renewables requires nothing less than an'energy revolution.' How and why did Europe's largest economy embrace a challenge that has been compared to the first landing on the moon? What does this transition entail? Is the German experience transferable to other industrialized nations such as the United States? Experts from business, academia, governmental agencies and non-profit think tanks offer multi-disciplinary perspectives on the experiences behind and the challenges ahead. They open up new viewpoints and avenues for shared insight on environmental governance, energy security, technological innovation, green landscape and urban design, as well as on the possibilities for transatlantic partnership and cooperation'--
Machine generated contents note: -- Introduction; Manuela Achilles and Dana Elzey -- PART I. BROADER CONTEXTS OF SUSTAINABLE DEVELOPMENT -- 1. Putting a Price on the Planet: Economic Valuation of Nature's Services; Mark White -- 2. International Trade and the Environment: Does Globalization Create Havens of Pollution?; Peter Debaere -- 3. New Directions in Green City Building; Timothy Beatley -- PART II. GERMANY'S ENERGY REVOLUTION -- 4. The German Green Party: From a Broad Social Movement to a People's Party; Arne Jungjohann -- 5. Germany's Ecological Tax Reform: A Retrospective; Michael Mehling -- 6.'Nuclear Power? No, Thank You!': Germany's Energy Revolution Post-Fukushima; Manuela Achilles -- 7. Ambitions and Realities of the German Energy Revolution; Brian Marrs -- PART III. TRANSATLANTIC COOPERATION AT THE MACRO AND MICRO LEVELS -- 8. The Transatlantic Climate Bridge: Challenges and Opportunities; Anja Kueppers-McKinnon, Georg Maue and Carmen Kristan -- 9. Formalizing the Transfer and Application of Environmental Policies and Lessons From Germany to the United States: The Case of Northern Virginia; Dale Medearis -- 10. Cultivating the Cross-Cultural Engineer: Key Insights; Dana M. Elzey and Kerstin Steitz -- 11. Designing for the Anthropocene: The Duisburg RhinePark; Jorg Sieweke -- 12. Eco-Revelatory Design: An Approach you Can Bank On; Eugene Ryang.
Includes bibliographical references and index.
Keywords: Energy policy -- Germany; Environmental policy -- Germany; Renewable energy sources -- Government policy -- Germany; Energy policy -- International cooperation; Environmental policy -- International cooperation; Renewable energy sources -- Government policy -- International cooperation; POLITICAL SCIENCE / Public Policy / General; POLITICAL SCIENCE / Government / National; POLITICAL SCIENCE / Public Policy / Environmental Policy; SCIENCE / Environmental Science